THE MEANING OF THE VERSES OF JIHAD COMMANDMENTS IN QS. AL-TAUBAH: JAKOBSON’S SEMIOTIC APPROACH TO STRENGTHENING RELIGIOUS MODERATION IN INDONESIA - Al Ghifari, Faishal; Muliadi, Muliadi (Universitas Nurul Jadid, 2024)
This research focuses on the importance of understanding the context of jihad to prevent misunderstandings that can trigger conflict in a multicultural society like Indonesia. QS. Al-Taubah has special characteristics that are full of jihad commands in a particular context that require in-depth analysis. This research aims to explore the meaning of the jihad message in QS. Al-Taubah using Jakobson’s semiotic approach, focusing on the communication context which includes sender, recipient, code, context, channel, and message. The research method used is a qualitative method with a library research approach. The data analysis technique utilizes Jakobson’s code and message theory to describe the communication elements in jihad verses. The implications of this research emphasize that a correct understanding of jihad verses can strengthen the principles of religious moderation in Indonesia, such as commitment to agreements, ethics in fighting, and the importance of diplomacy and resolving conflicts fairly. The research results show that the verses commanding jihad in QS. Al-Taubah have two main messages. First, thalab or orders from Allah swt to Muslims to wage jihad with specific goals that are influenced by certain contexts. Second, tahrikul himmah, namely motivation from Allah swt so that Muslims understand that the rewards in the afterlife are much better than worldly pleasures.